Hubungan Terapi Kombinasi Mood Stabilizer dan Antipsikotik dengan Kemampuan Fungsional Pasien Gangguan Afektif Bipolar di Rumah Sakit Jiwa Grhasia Yogyakarta : Relationship between Mood Stabilizer and Antipsychotic Combination Therapy with Functional Ability of Bipolar Affective Disorder Patients at Grhasia Mental Hospital Yogyakarta - Nadia Utami Noor; Dyah Aryani Perwitasari; Sawitri Sawitri (Jurnal Sains dan Kesehatan, 2021)
Bipolar disorder is a mental illness that can affect the functional abilities of the patients. It is persistent even in a euthymic condition. There have been number of studies on the effectiveness of mood stabilizer and antipsychotic therapy in bipolar disorder, but there is still few studies related to the effect of the combination therapy of mood stabilizer and antipsychotics on bipolar patient’s functional ability. The objectives of this study is to determine the associatioin of valproate and lithium combined with antipsychotics on functional ability of bipolar disorder patients at Grhasia Mental Hospital Yogyakarta. The study design was cohort retrospective. The data was collected from medical record. The subjects were patients who were hospitalized and undergone therapy combination mood stabilizer and antipsychotics in January-December 2018. Total of 46 patients, 38 received valproate + antipsychotic and 8 patients received lithium + antipsychotic. There was no significant association between the combination therapy group on the patient’s functional abilities [ Odds Ratio (OR) = 1,71; 95% Confidence Interval (CI): 0,37-7,95 ; p = 0,963].